ANALISIS PEMASARAN JERUK SIAM (Citrus nobilis) DI DESA GADINGREJO KECAMATAN UMBULSARI - Aida, Siti Nur; Hadi, Syamsul; Aulia, Anisa Nurina (Fakultas Ekonomi dan Bisnis, 2024)
Essentially, marketing is the process of moving products from manufacturers to customers. This study's goal is 1) to find out the marketing channels used for chayote, 2) to calculate marketing margins, 3) to determine marketing efficiency. This study's methodologies are descriptive and quantitative analysis. Purposively, Gadingrejo Village, Umbulsari District, Jember Regency was selected as the research location. 32 farmers and 12 marketing institutions make up the sample, which is selected using simple random sampling and total sampling. The study's findings indicate that: 1.) In Gadingrejo Village, chayote is marketed through two different channels, including the channel pattern to one Farmer – Wholesaler – Retailer – Consumer, the second channel pattern is Farmer – Collector Trader – Wholesaler – Retailer – Consumer, 2) The marketing margin in each marketing channel pattern has differences, namely a marketing margin of Rp 4,5000/kg is found in the first marketing channel pattern, and Rp 6,000/kg is found in the second, 3) The level II marketing channel pattern, with a farmer share value of 59.09%, has the highest marketing efficiency of any more efficient marketing channel pattern; in contrast, the level III marketing channel pattern, with a farmer share value of 45.45%, has the lowest marketing efficiency of any marketing channel pattern.